Successful thoracoscopic evacuation of an extrapleural hematoma with delayed symptomatic pleural effusion: a case report - Masanori Shimomura; Shunta Ishihara; Masashi Iwasaki; Masayoshi Inoue (Surgical Case Reports)
Abstract Background Traumatic extrapleural hematoma is a rare condition and is usually managed conservatively until spontaneous resolution unless active bleeding or expansion is found. Case presentation An 80-year-old man taking an anticoagulant medication was referred to our hospital after accidentally falling in a street ditch while riding a bike. Chest X-ray and computed tomography (CT) scan showed multiple fractures on ribs 7–9, hemothorax, and extrapleural hematoma in the posterior chest wall. Though the patient’s hemothorax was improved by chest tube drainage, the extrapleural hematoma still remained. He was transferred to another hospital for rehabilitation, but he was readmitted to our hospital because of dyspnea with accumulation of left pleural effusion, including a subpopulation of neutrophils, but without bacterial infection. We performed thoracoscopic evacuation of the hematoma on day 57 after the initial blunt chest trauma. The patient has had no recurrence of pleuritis for 6 months after surgery. Conclusion Since posttraumatic extrapleural hematoma may result in delayed secondary intractable pleural effusion causing dyspnea, careful observation is necessary when considering indications of surgical intervention.